Player Experience During the Junior to Senior Transition in Professional Football: A Longitudinal Case Study - Swainston, Scott C.; Wilson, Mark R.; Jones, Martin I. (Frontiers in Psychology, 2020)
The purpose of this study was to explore the evolving perspectives of young players going through the junior to senior transition in professional football. A primary objective was to adopt novel methods – weekly video diaries – to allow participants to control and report their own narratives as the transition unfolded over 40 weeks. Semi structured interviews, held at four time points, allowed the lead researcher to probe further on themes that were developing. Six participants from the academy volunteered to take part, but only the three who earned professional contracts completed the study. The primary themes in the academy were the pressure experienced waiting for the contract decision, and then preparation for senior football and the first team environment once contracts were awarded. Adaptation to senior football included not only increased physical and mental demands but also those related to the different style of play, the pressure to win, and how these both impacted decision-making. The football club set up two pathways to support this adaptation, loan moves and time with the U23’s. In the following season, the move to the senior squad was characterized by a lack of opportunity to play for the first team, resulting in additional loan moves. These moves, and the associated perceived lack of support structures, led to the participants experiencing issues with their club identity, their motivation and their confidence. Internal (mindset) and external (social support) coping strategies were developed over the study’s duration. Concluding comments from participants were related to greater acceptance of the need to be patient, perhaps reflecting on the club’s reputation of giving young players a sound football education. These phases of the transition came with ups and downs for each participant illuminating key elements of the adaptation to senior competition, barriers to transition without early success, and social aspects of the transition. Enhanced detail to these key areas poses important questions for future research and applied practice.